In the voices of the Sul-hween/Elders, on the Snuw’uyulh teachings of Respect : their greatest concerns regarding Snuw’uyulh today in the Coast Salish Hul’q’umi’num’ Treaty Group territory - Paige, Sharon Marlo (2009)
This research is based on the voices of the Hul’q’umi’num’ Sul-hween/Elders who participated on this project. They are of the Coast Salish people, specifically from the Hul’q’umi’num’ Treaty group area. The Sul-hween/Elders have significant concerns regarding the struggles that face the younger generations that surround them. They are concerned with the changes that are occurring in their culture and the fundamental principles of Snuw’uyulh. The Sul’hween/Elders discussed the effects of colonization and western society, what Snuw’uyulh means the importance of Snuw’uyulh and the teaching and learning style of Snuw’uyulh. The Sul-hween/Elders described the methods by which Snuw’uyulh can accompany and navigate an individual through childhood, puberty, parenting, grief and death. Snuw’uyulh is fundamental for unity, communication and family protocol.